ChemInform Abstract: The Synthesis of Chiral Fluorinated 4‐Alkyl‐4′‐[(4‐alkylphenyl)ethynyl]biphenyls. Issue 42 (1st October 2013) - Herman, Jakub; Kula, Przemyslaw
Abstract The copper‐catalyzed coupling between aryl Grignard reagents and alkyl bromides is optimized to provide intermediates for use in the synthesis of novel cholesteric liquid crystals.